Impact of Faculty Competences on the Quality of the Education Promoted - España Chavarría, Carolina (2011)
The following essay intends to demonstrate the impact of the teaching competences and the quality of the education provided, from an ethical perspective which, unlike the technical one, is the basis for teachers to: a) promote learning by processing information towards practical, clear and pertinent knowledge, and b) construct their own sense of education.